A STUDY ON TECHNOLOGY TREND OF CAMERA BY USING FI CODE IN JAPANESE PATENT - Ishii, Yoshie; Masuda, Koji; Hayashi, Yoshinori; Mitsuya, Teruaki; Haruyama, Shigeyuki (JEMIS (Journal of Engineering & Management in Industrial System), 2021)
In development of technology and product, it’s important to make decisions based on technology trend. Some previous studies obtained technology trend based on patent information. In our previous study, we tried to investigate the state of innovation and the emergence of dominant design by using patent information. We analyzed inkjet printers and NC machines with theme codes and F term codes in Japanese patent classification codes. In this study, we tried to know the change of technology of other products other than inkjet printers or NC machines by using patent information. The target product of this study is camera. Camera products changed its key technology of imaging and recording from analogue film to digital imaging sensor and semiconductor memories. We attempted to obtain this change by using patent information.